African discourse in Islam, oral traditions, and performance [ - Abdul-Rasheed Na'Allah (African studies, 2010)
Develops an African indigenous discourse paradigm for interpreting and understanding literary and cultural materials. This work is suitable for scholars and students of African culture and literature.